Stimulus Kelompok Orangtua Siswa SD Ar Rasyid dalam Menciptakan Masyarakat Produktif Ekonomi - Ruri Aditya Sari; Iswandi Idris; Syahril; Agnita Yolanda; Nurismilida (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Women are given chance to do as carreer women and housewives. However, some women got married in productive ages choose to be a career woman. A group of mothers in TK Ar Rasyid Tanjung Selamat, Sunggal,Deli Serdang, there are 15 mothers with 27-35 years old unproductive society financially become partners of stimulus community dedication. It aims to help group of students' mothers, additional knowledge, skill, welfares through income commission and help partners to spend their leisure Time by doing meaningful activities both physically and mentally. Some solutions are offered, such as cooking healthy meals training to gain value for sale and modern with low budget. They are like rolled age,BBQ fried chicken training, bread pudding training,online marketing and deciding prices training and also arranging treasury. Through this stimulus community dedication,it would add partenrs' knowledge 80% and partners' creativity improved up to 65%.